Electro-optic and dielectric properties of a ferroelectric liquid crystal doped with chemically and thermally stable emissive carbon dots. Issue 43 (14th May 2015) - Shukla, R. K.; Mirzaei, J.; Sharma, A.; Hofmann, D.; Hegmann, T.; Haase, W.
<x xml:space="preserve">Abstract</x> Dispersion of the C-dots in n-hexane under ambient light and under 366 nm illumination indicating the bright photoluminescence of the C-dots; PL spectra of C-dots at different excitation wavelengths (360 nm to 540 nm) increasing at 20 nm intervals.